2016
DOI: 10.1109/jstqe.2015.2513667
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography for Brain Imaging and Developmental Biology

Abstract: Optical coherence tomography (OCT) is a promising research tool for brain imaging and developmental biology. Serving as a three-dimensional optical biopsy technique, OCT provides volumetric reconstruction of brain tissues and embryonic structures with micrometer resolution and video rate imaging speed. Functional OCT enables label-free monitoring of hemodynamic and metabolic changes in the brain in vitro and in vivo in animal models. Due to its non-invasiveness nature, OCT enables longitudinal imaging of devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 223 publications
(271 reference statements)
1
38
0
Order By: Relevance
“…Utilizing low-coherence light in the near-infrared region, OCT features a microscale spatial resolution with an imaging depth at millimeter level in scattering tissues [24], bridging the gap of imaging scales between the confocal and acoustic imaging techniques. This unique spatial imaging scale of OCT has enabled applications ranging from biomedical research [25][26][27] to clinical diagnosis and monitoring [28][29][30]. Embryology is a major research area where OCT shows great promise as a high-resolution unlabeled imaging tool [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing low-coherence light in the near-infrared region, OCT features a microscale spatial resolution with an imaging depth at millimeter level in scattering tissues [24], bridging the gap of imaging scales between the confocal and acoustic imaging techniques. This unique spatial imaging scale of OCT has enabled applications ranging from biomedical research [25][26][27] to clinical diagnosis and monitoring [28][29][30]. Embryology is a major research area where OCT shows great promise as a high-resolution unlabeled imaging tool [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrahigh resolution has remarkable characteristics for detecting microstructure in OCT imaging. OCT has been widely used in brain imaging (36)(37)(38). Bizheva et al reported that UHR OCT was investigated for imaging of brain tissue morphology using a number of animal models ex vivo and in vitro (39).…”
Section: Brain Nerve Fiber Bundle Imaging Based On Functional Oct/ocmmentioning
confidence: 99%
“…Optical coherence tomography can visualize the detailed structure of different biological tissue samples [2] such as brain cytoarchitecture [3], large cellular structures (e.g., [4,5]), or retinal layers in the eye ( [6][7][8] to name a few) or functional retinal images (e.g., [9,10]). In addition, it can provide functional information by capturing the vascular morphology through optical coherence angiography (e.g., [11][12][13][14]) or by recording vascular blood velocity (e.g., [15][16][17][18]).…”
Section: Introductionmentioning
confidence: 99%
“…While the theory and applications of SD-OCT are vastly presented in many great literatures (e.g., [2,[35][36][37][38][39][40][41][42][43][44]), the lack of a detailed discussion on optical design and practical implementation guidelines of this device precludes the utilization of SD-OCT scanners by many researchers. In this paper, we review the fundamental concepts of SD-OCT image formation and propound practical considerations for the design and implementation of the device, along with some guidelines for choosing proper components to obtain the desired image quality.…”
Section: Introductionmentioning
confidence: 99%